(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
The Latakia region is characterized by the diversity of the geographical and topographic sections, including coasts, beaches, plateaus and mountains. This diversity is reflected in the diversity of climate and landscape and helps in the formation of rivers, streams and lakes as a result of rain and the topographic gradient, which gives the region tourist importance. It also contains many important archaeological, historical and cultural sites. The study aimed to determine the distribution pattern of natural and human tourist destinations and the direction of their spread. In determining the factors of tourist attractions, the study relied on a random sample questionnaire that includes individuals present in the most important tourist destinations in the study area. The study showed that 58.8% of the most important natural tourist destinations are distributed over the equivalent of 52% of the area of ​​the Latakia region, and that 48.2% of the most important human tourist destinations are distributed over the equivalent of 68.2% of the area of ​​the studied region, and thus the pattern of distribution of destinations. Human tourism is randomly dispersed, as is the case with natural tourist destinations, but human destinations are distributed more widely. The study concluded that most of the tourist destinations that tourists visit contain more than one attraction factor, and the results showed that the tourist is not looking for a specific goal in his visit to the tourist destination, but rather a set of goals. It also showed that the tourist destinations in the study area suffer from a lack of services that affects It greatly enhances the tourist attraction of the area.